THE INFLUENCE OFLEADERSHIP STYLE AND WORK MOTIVATION TOWARD JOB SATISFACTION AND THE IMPLICATION TOWAD EMPLOYEE PERFORMANCE - Panjaitan, Saur; Hidayat, Rahmat (Strategic Management Business Journal, 2023)
The formulation of the problem in this study is the Influence of Leadership Style and Work Motivation on Job Satisfaction which Has Implications for Employee Performance at PT Haier Electrical Appliances Indonesia. This type of research is quantitative research. The number of samples is 88 employees. This study uses the Lisrel 8.8 data processing application. The results of this study are (1) Leadership Style has no effect on Job Satisfaction, (2) Work Motivation has no effect on Job Satisfaction, (3) Leadership Style and Work Motivation simultaneously have an effect on Job Satisfaction, (4) Leadership Style has an effect on Performance Employees, (5) Work Motivation influences Employee Performance, (6) Job Satisfaction does not affect Employee Performance, and (7) Leadership Style, Work Motivation, and Job Satisfaction simultaneously influence Employee Performance. JEL Classification: M10, M21, M51